Privata markägares reflektioner med hänseende till den minskade röjningsaktiviteten : så kan skogsvårdsstyrelsen anpassa sitt arbete - Karlsson, Frida (SLU/Dept. of Forest Products, 2006)
This project was a request of Norrbodal´s Forestry Board, Västra Götaland. It was performed as a qualitative interview analysis of private forest owner's deficient motivation regarding pre-commercial thinning. The purpose of the project is to investigate what the Forestry Board can do to motivate private forest owners to do more pre-commercial thinning.